Pesan Al Quran dalam Kerjasama Musa dengan Syuayb tentang Pengelolaan Bisnis - Mesra, Alimin (Faculty of Shariah and Law, 2012)
Prophet Moses and Prophet Syuayb companion ultimately led them to work together. This case reveals a number of values that should be developed and applied in life related to business management. This story reveals a relation between employees and owners of capitla, recruitment patterns, appreciation of performance, proffesionalism, and some related matters. The cooperation between them can be considered as a symbolic learning delivered by the Quran, especially in business development. This story also shows that a partnership should be based on a clear contract that shows such related materials, working period, the amount of wages, security, and others related to their right and obligation.DOI: 10.15408/aiq.v4i1.2080